2017
DOI: 10.1186/s13002-017-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of Nucularia perrinii Batt. (Chenopodiaceae) in the camel-based Sahrawi social-ecological system

Abstract: BackgroundPastoral social-ecological systems (SESs) are adaptive and complex systems rooted in the extensive exploitation of forage plants for livestock-based livelihoods and culture. There are species and relations that are foundational to the existence of these SESs. Nucularia perrinii Batt. (Chenopodiaceae) is an endemic halophyte plant of central and western Sahara seldom cited in the scientific literature. The objective of this study was to investigate the role of this plant in the SES of the Sahrawi came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, in Iraq, Kurdish pastoralists were found to consume more snacks than the neighboring more horticulturalist-driven Kakei [22] and much more than Assyrians [23]. Even more specifically, Volpato and Di Nardo [24] explored the pivotal relation between the Sahrawi camel nomads and a specific savannah plant in Western Sahara. Yet, the pastoral activity, if not properly managed, can also negatively affect the presence of wild edible plants [25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Iraq, Kurdish pastoralists were found to consume more snacks than the neighboring more horticulturalist-driven Kakei [22] and much more than Assyrians [23]. Even more specifically, Volpato and Di Nardo [24] explored the pivotal relation between the Sahrawi camel nomads and a specific savannah plant in Western Sahara. Yet, the pastoral activity, if not properly managed, can also negatively affect the presence of wild edible plants [25].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, humans (e.g., local agro-pastoralists) and nature (e.g., forage species) have co-existed, leading to development of adaptive and complex social-ecological systems—SESs [ 21 ]. These adaptive and intricate (agro-)pastoralists’ SESs are hinged on extensive utilization of available natural forage plants for their livestock-based livelihoods and culture [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of traditional forage plant resources used by immigrants refers to the types, quantity, and parts of traditional forage plants that can be used as forage [2, 9, 36], which depends, to a certain extent, on the distribution of forage plant resources around the area they live. The related knowledge includes the knowledge about forage forms of, seasonal use of, suitable livestock for traditional forage plants, and classification of pasture habitats [1, 5, 8, 37–40], which is affected by certain cultural factors, such as livestock rearing and breeding habits, as well as traditional techniques. Previous studies have concluded that the factors affecting traditional plant resources and associated knowledge include the natural environment (ecosystem [41]), traditional culture [42], customs and habits [43], the theoretical system of traditional food and medicine [10, 44], traditional production and lifestyle [45, 46], and degree of modernization [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…This plays an important role in maintaining the positive development of agricultural and animal husbandry socioecological systems [3]. Local farmers’ and herdsmen’ traditional knowledge of forage plants, gained from local livelihoods and cultures that rely on natural herbage [4], plays an important role in regional biodiversity protection [5]. Farmers and herdsmen in areas with a long history of rearing livestock have a rich knowledge of forage plants, which has been recorded in the countries such as Morocco, West Africa, Brazil, Ethiopia, Pakistan, and Austria [2, 4, 610] to provide techniques and strategies for utilization, classification management, and sustainable development of forage plant resources.…”
Section: Introductionmentioning
confidence: 99%